2023
DOI: 10.1161/circresaha.122.321849
|View full text |Cite
|
Sign up to set email alerts
|

USP25 Ameliorates Pathological Cardiac Hypertrophy by Stabilizing SERCA2a in Cardiomyocytes

Abstract: BACKGROUND: Pathological cardiac hypertrophy can lead to heart failure and is one of the leading causes of death globally. Understanding the molecular mechanism of pathological cardiac hypertrophy will contribute to the treatment of heart failure. DUBs (deubiquitinating enzymes) are essential to cardiac pathophysiology by precisely controlling protein function, localization, and degradation. This study set out to investigate the role and molecular mechanism of a DUB, USP25 (ubiquitin-specific pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Atrogin‐1 promoted ubiquitination of calcineurin, thereby inhibiting cardiomyocyte hypertrophy 116 (Figure 5). According to Ye et al., the deubiquitinating enzyme ubiquitin‐specific peptidase 25 (USP25) can combined with SERCA2a and prevent proteasomal pathway from degrading it 117 . This process not only maintained calcium homeostasis in cardiomyocytes but also contributed to the inhibition of cardiac hypertrophy.…”
Section: Protein Ubiquitination In Diabetic Cardiomyopathymentioning
confidence: 99%
“…Atrogin‐1 promoted ubiquitination of calcineurin, thereby inhibiting cardiomyocyte hypertrophy 116 (Figure 5). According to Ye et al., the deubiquitinating enzyme ubiquitin‐specific peptidase 25 (USP25) can combined with SERCA2a and prevent proteasomal pathway from degrading it 117 . This process not only maintained calcium homeostasis in cardiomyocytes but also contributed to the inhibition of cardiac hypertrophy.…”
Section: Protein Ubiquitination In Diabetic Cardiomyopathymentioning
confidence: 99%
“…[110,[223][224][225][226][227][228][229] Although the exact binding mode of most protein ligands for dectin-1 is still an open question, the interaction of human dectin-1 with CLEC-2 has been mapped to a distinct interactions motif in the stalk of dectin-1 and binding sites of annexins and angiotensin II appears to be different from the binding site of βglucan. [110,224,226] Dectin-1 illustrates how a binding site distinct from canonical Ca 2 + -dependent carbohydrate recognition site mediates glycan binding and becomes the primary binding site for the role of dectin-1 as a pattern recognition receptor. Moreover, the existence of multiple protein ligands with potentially more distinct binding sites underlines the functional variability of the CTLD fold.…”
Section: Example 3: Mglmentioning
confidence: 99%
“…Research showed that USP25, as a protective protein of the heart, played an anti-hypertrophic role in pathological myocardial hypertrophy (Ref. 55 ). Ye et al found that knocking out USP25 in mice exacerbated myocardial hypertrophy induced by angiotensin II and TAC.…”
Section: Role Of Deubiquitinases In Cardiac Diseasementioning
confidence: 99%
“…USP25 stabilized intracellular calcium homeostasis and alleviated myocardial hypertrophy by removing the K48-linked ubiquitin chains of SERCA2a protein (Ref. 55 ). Coincidentally, the team also found that JOSD2 maintained myocardial calcium homeostasis by upregulating SERCA2a, thereby attenuating cardiac hypertrophy (Ref.…”
Section: Role Of Deubiquitinases In Cardiac Diseasementioning
confidence: 99%